2007
DOI: 10.15517/rbt.v56i4.5758
|View full text |Cite
|
Sign up to set email alerts
|

Composición taxonómica y relaciones zoogeográficas de los peces demersales de la costa occidental de Baja California Sur, México

Abstract: Taxonomic composition and zoogeographic relations of demersal in the western coast of Baja California Sur, Mexico. The composition of demersal fish along the western coast of the State of Baja California Sur, México, including the limit of the northern distribution of the ichthyofauna of the eastern tropical Pacific, is presented. The survey was carried out on four oceanographic cruises between autumn 2004 and March 2006. Of 220 species in 132 genera and 73 families, 26.3% are species of wide distribution from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
0
9
0
16
Order By: Relevance
“…Hornyhead turbot migrated into deeper waters during the El Niño event of 1987-1988(Allen, 2008. Rodríguez-Romero et al (2008) consider this species as very common in the west coast of Baja California, with sizes ranging between 81 and 256 mm SL. In San Quintin Bay, Rosales-Casián (1996) reported sizes between 60 and 140 mm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hornyhead turbot migrated into deeper waters during the El Niño event of 1987-1988(Allen, 2008. Rodríguez-Romero et al (2008) consider this species as very common in the west coast of Baja California, with sizes ranging between 81 and 256 mm SL. In San Quintin Bay, Rosales-Casián (1996) reported sizes between 60 and 140 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have been reported on Baja California Pleuronectidae, providing general information on the zoogeography Eschmeyer, 1998;Rodríguez-Romero et al, 2008) and distribution (Kramer, 1991;Rosales-Casián, 1996;Rábago-Quiroz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Los estatus taxonómicos en peces con un enfoque de composición, ubicación, caracterización y zoogeografía son fundamentales para desarrollar cualquier tema de biodiversidad y manejo pesquero (Aguilar-Palomino et al 1996;Rodríguez-Romero et al 2008). Este estudio aporta información al conocimiento de la fauna íctica demersal de zonas profundas (90 a 540m) de la región oriental del Golfo de California.…”
Section: Discussionunclassified
“…El análi-sis de afinidad zoogeográfica fue determinada de acuerdo con el esquema básico de Briggs (1974de Briggs ( , 1995, con modificaciones de Boschi (2000), Galván et al (2000), Hastings (2000), Robertson & Allen (2002), Robertson et al (2004) Nelson et al (2004), Love et al (2005), Rodríguez Romero et al 2008. Se presenta el nivel trófico, afinidad biogeográfica y las tallas máximas conocidas para las especies.…”
Section: Materiales Y Métodosunclassified
“…The Mexican Pacific comprises three mayor regions: The West coast of the Baja California peninsula (BC), a transitional zone in faunal composition and environmental conditions (Rodríguez-Romero, Palacios-Salgado, López-Martínez, Hernández-Vázquez, & Ponce-Díaz, 2008), influenced by the California Current, the subsurface California Countercurrent and the North Equatorial current (OMZ: 300 -1 800 m depth) (Levin, 2003;Fiedler & Talley, 2006). The Gulf of California (GC) is a semi-closed sea, with strong processes of horizontal transport and vertical mixing of water in its Northern part (Palacios-Hernández, Beier, Lavín, & Ripa, 2002), while in its central and southernmost portions, the OMZ is located between 250 and 1 400 m depth, and between 70 and 1 300 m depth, respectively, with a hypoxic-anoxic zone (150-700 m depth), being an impenetrable barrier for some species (Zamorano et al, 2006;Mendez, 2007;Hendrickx & Serrano, 2010).…”
mentioning
confidence: 99%